In defense of anarchism - Wolff, Robert Paul.; Paul Avrich Collection (Library of Congress) (New York, Harper & Row, 1970)
In Defense of Anarchism is a 1970 book by the philosopher Robert Paul Wolff, in which the author defends individualist anarchism. He argues that individual autonomy and state authority are mutually exclusive and that, as individual autonomy is inalienable, the moral legitimacy of the state collapses.
includes index.
Keywords: Authority; Democracy; Anarchism; State, The